Cervical pregnancy- A conservative approach - Shastri, Shraddha; Junnare, Ketaki K; Shekhawat, GS (Asian Journal of Medical Sciences, 2016)
A case of cervical pregnancy responded well to intramuscular Methotrexate therapy is presented. It is suggested that, in cervical pregnancies in which fertility preservation is desired, a stepwise conservative approach should be applied before resorting to surgical intervention. Asian Journal of Medical Sciences Vol.7(4) 2016 104-106